ANALISIS PENGENDALIAN KUALITAS PRODUK REJECT PADA PT PIPA MAS PUTIH BATAM - Maro, Abner; ARSYAD SUMANTIKA (Computer Science and Industrial Engineering, 2024)
This study talks about the investigation of Coupling item quality control at PT PIPA MAS PUTIH BATAM is an OCTG creation organization as one of the coupling items result of PT. PMP. The organization upholds pipeline needs for oil and gas organizations. Since the nature of the item is a vital model involved by clients in deciding the item to be utilized. This study plans to figure out what causes absconds during the coupling creation interaction and what are the elements that cause these deformities. Examination of creation information handling and imperfection item information is done utilizing the Disappointment mode impact investigation (FMEA) and shortcoming tree investigation (FTA) strategies which are needs for development, to be specific in the coupling item process. A few issues have surrenders in OCTG items (particularly Coupling) in the 2022-2023 period. The consequences of the investigation of the quantity of imperfection items surpass the organization's foreordained guidelines for a most extreme deformity of 2% each year. It is common knowledge that environmental, mechanical, and human factors all contribute to disability. Proposed upgrades are the foundation of occasional machine upkeep plans, endeavors to refresh new machines and slicing apparatuses to increment great outcomes, and increment the quantity of workers in significant pieces of the cycle. Keywords: COUPLING, FMEA, FTA